Thyroid uptake and scintigraphy using 99mTc pertechnetate: standardization in normal individuals. - Ramos, Celso Darío (2002)
CONTEXT: Thyroid uptake and scintigraphy using 99mTc-pertechnetate has proven to be more advantageous than with 131I-iodide, since the images have better quality, the procedure is faster and the patient is submitted to a lower radiation dose. OBJECTIVE: The purpose of this study was to standardize a simple and fast methodology for performing thyroid uptake and scintigraphy and to determine the normal values for 99mTc-pertechnetate uptake. TYPE OF STUDY: Prospective, non-randomized. SETTING: Division of Nuclear Medicine, Department of Radiology, School of Medical Sciences, Campinas State University. PARTICIPANTS: The study consisted of 47 normal individuals, 30 women and 17 men, with ages ranging from 19 to 61 years (mean of 33 years). PROCEDURES: The laboratory assessment of thyroid function consisted of serum dosages of ultra-sensitive thyroxin and thyrotrophin. Twenty minutes after an intravenous injection of 10 mCi (370 MBq) of 99mTc-pertechnetate, the images were obtained on a computerized scintillation camera equipped with a low-energy high-resolution parallel hole collimator. RESULTS: All the individuals were euthyroid both on clinical and laboratory evaluation. The baseline thyroid 99mTc-pertechnetate uptake ranged from 0.4 to 1.7%. The uptake values obtained in these normal individuals showed that 95% presented a thyroid uptake that ranged from 0.4 to 1.5% of the injected dose. CONCLUSION: The assessment of thyroid structure and function using 99mTc-pertechnetate is a simple, fast and efficient method, which could easily become a part of the routine studies in nuclear medicine laboratories.